Trends in chronic kidney disease and calories from ultra-processed foods: NHANES at the highly granular level - Kristin E. Leonberg; Manish R. Maski; Tammy M. Scott; Yutong Chen; Bingjie Zhou; Elena N. Naumova (Discover Public Health)
Abstract Background Chronic kidney disease (CKD) is a significant public health challenge influenced by genetic predispositions and lifestyle factors, including unhealthy diets. Recent research highlights a link between ultra-processed food (UPF) consumption and increased CKD risk. UPFs, often rich in calories, added sugars, unhealthy fats, sodium, and additives, may impair kidney health and accelerate disease progression. We examined changes in eGFR and UPF over time, focusing on high-risk groups and the impact of UPF on kidney function decline and projected eGFR and UPF intake in 2030 using NHANES data from U.S. adults. Methods Quasi-Poisson regression models with robust estimators were applied to NHANES participants (> 20 years, with complete dietary data and creatinine values) from 2003 to 2017 to assess the relationship between estimated individual eGFR and calories from ultra-processed foods (UPFc). We applied a sequential model building approach incorporating time-fixed and time-varying socioeconomic and sociodemographic variables for the total sample and each race/ethnic group. Results Each NHANES cycle showed a steady increase in eGFR (RR = 1.026; 95% CI 1.019–1.033) and UPFc (RR = 1.038; 95% CI 1.014–1.062) for the overall sample for fully adjusted models. A 10% increase in calories consumed from UPFs was associated with a significant decline in eGFR (RR = 0.9934, 95% CI 0.9925–0.9943), with notable differences among White, Black, Mexican, and Other race groups. Conclusion Higher UPFc and aging are linked to a steady decline in eGFR. Older adults, particularly White and Black males and females, show greater vulnerability, indicating the need for dietary guidelines to mitigate CKD progression.